2020
DOI: 10.1101/2020.10.21.348185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The RNA-binding protein HuR promotes nonalcoholic steatohepatitis (NASH) progression by enhancing death signaling pathway

Abstract: Hepatocyte death triggers liver inflammation, liver injury, and fibrosis, which contributes to non-alcoholic steatohepatitis (NASH) pathogenesis. However, whether RNA processing regulates death signaling pathway during NASH progression is not investigated. In this study, we show that HuR, a widely expressed RNA-binding protein, promotes NASH progression by increasing DR5/caspase8/caspase3-mediated hepatocyte death. Cytosolic HuR levels are abnormally elevated in human patients with NASH. Hepatocyte-specific de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Sirtuin 1, encoded by the SIRT1 gene, can deacetylate an RNA-binding protein quaking 5 (QKI 5), which inhibits TG synthesis in vivo and in vitro via the PPARα/FoxO1 signaling pathway and suppresses NAFLD progression in mice [96]. Another study showed that a broadly expressed RNA-binding protein human antigen R (HuR) can accelerate NASH progression by increasing death receptor 5 (DR5)/caspase 8/caspase 3-mediated hepatocyte death and liver injury [97].…”
Section: Rna-binding Proteinsmentioning
confidence: 99%
“…Sirtuin 1, encoded by the SIRT1 gene, can deacetylate an RNA-binding protein quaking 5 (QKI 5), which inhibits TG synthesis in vivo and in vitro via the PPARα/FoxO1 signaling pathway and suppresses NAFLD progression in mice [96]. Another study showed that a broadly expressed RNA-binding protein human antigen R (HuR) can accelerate NASH progression by increasing death receptor 5 (DR5)/caspase 8/caspase 3-mediated hepatocyte death and liver injury [97].…”
Section: Rna-binding Proteinsmentioning
confidence: 99%